ELECTRONIC MUNICIPALITY AS THE SELF-GOVERNMENT REFORMATION ELEMENT - Manvelidze I.; Tebidze M. (World Science, 2019)
There still exist some problems regarding municipality transparency provision, public engagement in political communication and municipality service transparency in Georgia. Unfortunately, local government bodies lack special skills and techniques to build up transparent and effective relationship with citizens.